2013
DOI: 10.1128/jvi.03507-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Transfection- and Infection-Derived Simian Immunodeficiency Virus Challenge Stocks for In Vivo Nonhuman Primate Studies

Abstract: h Simian immunodeficiency virus (SIV) stocks for in vivo nonhuman primate models of AIDS are typically generated by transfection of 293T cells with molecularly cloned viral genomes or by expansion in productively infected T cells. Although titers of stocks are determined for infectivity in vitro prior to in vivo inoculation, virus production methods may differentially affect stock features that are not routinely analyzed but may impact in vivo infectivity, mucosal transmissibility, and early infection events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 47 publications
(48 reference statements)
1
104
0
Order By: Relevance
“…In contrast to D470N and E84K, G62N was enriched in CD4-depleted animals at both day 11 and day 42 but was not significantly associated with CD4-independent entry. G62N is present at an overall frequency of 4% to 5% among SIVmac sequences and occasionally represents the dominant sequence among some SIVmac251 swarms (33,34). Thus, additional selective forces in the CD4-depleted animals other than CD4 independence per se appear to be responsible for selection at this residue.…”
Section: Bodies In the Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to D470N and E84K, G62N was enriched in CD4-depleted animals at both day 11 and day 42 but was not significantly associated with CD4-independent entry. G62N is present at an overall frequency of 4% to 5% among SIVmac sequences and occasionally represents the dominant sequence among some SIVmac251 swarms (33,34). Thus, additional selective forces in the CD4-depleted animals other than CD4 independence per se appear to be responsible for selection at this residue.…”
Section: Bodies In the Cd4mentioning
confidence: 99%
“…Only one day 42 Env from a CD4-depleted animal did not mediate appreciable CD4-independent entry (RZj5.D42.9.2) and did not carry D470N, E84K, or any previously described polymorphism(s) associated with CD4 independence. G62N, E84K, and D470N have not been explicitly characterized in previous studies, but an analysis of SIVmac sequences revealed that G62N has ϳ5% frequency within SIVmac251 viral stocks (31)(32)(33)(34), while D470N and E84K are extremely rare and present mainly in in vivo-passaged SIVmac251-related isolates (34)(35)(36)(37)(38). Of note, all instances of G62N, E84K, and D470N that arose in these animals were the result of G-to-A nucleotide changes (Fig.…”
Section: Fig 1 Envs From Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to assess if these 4 amino acid substitutions affected the incorporation of Env glycoproteins by virions, SIVsmE543-3 and SIVsmE543CT clones were purified, concentrated, and examined by SDS-PAGE using a dual-color fluorescent imaging method ( Figure 5A), and the ratio of virion p27 content against virion gp120 content was calculated ( Figure 5B and refs. 27,28). The levels of virion-incorporated Env protein between SIVsmE543-3 and SIVsmE543CT clones were not significantly different, indicating that the mutations we have identified as enhancing replication in macrophages do not influence the virion incorporation of Env.…”
Section: Assessment Of Virion-incorporated Env Levelsmentioning
confidence: 72%
“…Quantitative measurements of viral p27 capsid (CA) and gp120 protein in virions for determinations of Gag/Env ratio were determined using dual-color fluorescent protein gel analysis as previously described (27,28). Briefly, SIVsmE543-3 and SIVsmE543CT clones were expanded in CEM cells, concentrated and purified, and examined by SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%